A Comprehensive Review of Cardiac Tumors: Imaging, Pathology, Treatment, and Challenges in the Third Millennium - Andrea De Martino; Claudia Pattuzzi; Sara Garis; Francesca Bosco; Vittorio Maria Virgone; Antonio Salsano; Francesco Santini; Angela Pucci (Diagnostics)
Cardiac tumors represent rare neoplasms, but they include a very wide range of neoplasia—first primary benign and malignant cardiac tumors, then cardiac metastases, with these latter ones being far more common in adulthood. These diagnoses may be challenging because of frequently non-specific signs and symptoms; for example, their clinical management may be difficult because of the site and because of possible hemodynamic or arrhythmogenic consequences, independent from their biology. Cardiac tumors may be asymptomatic and incidentally diagnosed, or they may cause heart failure, life-threatening arrhythmias, or even sudden cardiac death. Although they may still represent a post-mortem finding, the evolution and the larger use of cardiac imaging tools, initially echocardiography, has progressively and significantly increased their in vivo detection. Magnetic resonance imaging and computed tomography may give crucial information as to the composition and localization of cardiac masses, useful for investigating them and for planning surgery. Histology is mandatory for the definite and differential diagnosis of the cardiac masses, for assessing predictive factors in malignancies, and for then establishing the appropriate management of patients. Modern techniques applied to histology, including immunohistochemistry and molecular biology, may be required to characterize cardiac tumors, to properly classify them and to assess predictive and/or prognostic markers. Surgical procedures, including minimally invasive surgery, have also dramatically evolved in the last decades, allowing adequate treatment in most cardiac tumors. Finally, biopsy may be useful in selected cases, particularly when radical surgery is not feasible, and histological diagnosis is fundamental for other possible therapeutic approaches. The scope of this review covers advancements in the imaging diagnosis, histology, and treatment of primary and secondary cardiac tumors.